Retail management - Fronda, Jennifer G.; Pascual, Marilou P.; Villacorte, Rhea M. (Mutya Publishing House, Inc., 2013)
"This worktext provides different topics about Retail Management which could aid students in comprehending the world of Retailing. Questions and activities are provided at the end of every chapter in order to evaluate the students' comprehension and to augment their knowledge regarding the subject"--Preface.